2018
DOI: 10.5603/gp.a2018.0038
|View full text |Cite
|
Sign up to set email alerts
|

The role of new adipokines in gestational diabetes mellitus pathogenesis

Abstract: Gestational diabetes mellitus (GDM) is defined as any degree of glucose intolerance with onset or first recognition dur-ing pregnancy. Explanation of the GDM pathogenesis is important due to preventing gestational complications. During pregnancy there are significant changes in maternal metabolism. Many of these changes are influenced by different adi-pokines produced in the placenta and adipose tissue. The exact role of adipokines in the pathogenesis of GDM remains still unknown. Several adipokines have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…The exact mechanisms through which synbiotics and probiotics exert their anti‐oxidative properties remain largely unknown; but (a) preventing and reducing ascorbate auto‐oxidation and metal ion chelation, (b) reducing the activity of superoxide anion radicals, hydrogen peroxide and reactive oxygen species, (c) preventing the formation of lipid hydro‐peroxides, and (d) improving the anti‐inflammatory factors through production of SCFA in the gut are some of the probable mechanisms 57‐60 . Studies have reported a relationship between reduction of serum adiponectin concentrations and the risk of GD which might be due to the reduction of insulin sensitivity and anti‐inflammatory effects 61,62 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact mechanisms through which synbiotics and probiotics exert their anti‐oxidative properties remain largely unknown; but (a) preventing and reducing ascorbate auto‐oxidation and metal ion chelation, (b) reducing the activity of superoxide anion radicals, hydrogen peroxide and reactive oxygen species, (c) preventing the formation of lipid hydro‐peroxides, and (d) improving the anti‐inflammatory factors through production of SCFA in the gut are some of the probable mechanisms 57‐60 . Studies have reported a relationship between reduction of serum adiponectin concentrations and the risk of GD which might be due to the reduction of insulin sensitivity and anti‐inflammatory effects 61,62 …”
Section: Discussionmentioning
confidence: 99%
“… 57 , 58 , 59 , 60 Studies have reported a relationship between reduction of serum adiponectin concentrations and the risk of GD which might be due to the reduction of insulin sensitivity and anti‐inflammatory effects. 61 , 62 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Имеются исследования, подчеркивающие различия влияния концентраций адипонектина в зависимости от пола будущего ребенка. Известно, что половой диморфизм возникает во время развития плода [17,43,44]. Согласно результатам исследования, могут существовать различия в механизмах, связанных с развитием массы жира новорожденных мальчиков и девочек.…”
Section: гендерно-специфическая связь материнского адипонектина с мас...unclassified
“…W chwili obecnej trwają badania nad nowymi adipocytokinami, takimi jak: nesfatyna-1, chemeryna, ghrelina, waspina, wisfatyna, omentyna czy RPB-4 (ang. Retinol Binding Protein 4) [17,18]. Najlepiej poznane do tej pory adipocytokiny (leptyna czy adiponektyna) powodują pojawienie się insulinooporności w prawidłowo rozwijającej się ciąży, jednak dokładny mechanizm ich działania nie został do końca wyjaśniony.…”
unclassified